2016
DOI: 10.1158/2159-8290.cd-15-1105
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Oncogenic KRAS Output with Small Molecules Targeting the Inactive State

Abstract: KRAS gain-of-function mutations occur in approximately 30% of all human cancers. Despite more than 30 years of KRAS-focused research and development efforts, no targeted therapy has been discovered for cancers with KRAS mutations. Here, we describe ARS-853, a selective, covalent inhibitor of KRAS G12C that inhibits mutant KRAS-driven signaling by binding to the GDP-bound oncoprotein and preventing activation. Based on the rates of engagement and inhibition observed for ARS-853, along with a mutant-specifi c ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
669
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(725 citation statements)
references
References 35 publications
33
669
0
3
Order By: Relevance
“…10,13,14 More recently, the Ras G12C was shown to actively cycle in a "hyper-excitable" state in cells, illustrating that some undesirable features of oncogenic alleles may only be manifest in a cycling network context. 15 In agreement with this, we found that the network context was critical for revealing differences between oncogenic and wildtype alleles of Ras (Fig. 3).…”
supporting
confidence: 83%
“…10,13,14 More recently, the Ras G12C was shown to actively cycle in a "hyper-excitable" state in cells, illustrating that some undesirable features of oncogenic alleles may only be manifest in a cycling network context. 15 In agreement with this, we found that the network context was critical for revealing differences between oncogenic and wildtype alleles of Ras (Fig. 3).…”
supporting
confidence: 83%
“…Further research is required to understand KRAS mutations and to develop drugs targeted against them (6). Some recent investigations have generated a renewed interest in the development of direct KRAS inhibitors (19). For instance, Lito and colleagues (20) achieved blockade of nucleotide exchange factors from activating KRAS.…”
Section: Kras Mutations As a Predictive Factor Of Resistancementioning
confidence: 99%
“…More recent work has connected increased glucose metabolism to oncogene activation (12), setting the stage for numerous studies detailing the role of oncogenes and tumor suppressors in regulating cancer cell metabolism to promote the accumulation of biomass necessary for enhanced proliferation (13)(14)(15). Because drugs are lacking to specifically treat patients with tumors harboring many mutations in genes such KRAS and TP53, one hope is to identify other pathway dependencies in these cancers (16)(17)(18). Both KRAS and TP53 mutations result in metabolic changes, and efforts to target the downstream metabolic effects of these events have demonstrated preclinical potential and led to development of drugs in current clinical trials (19,20).…”
Section: Introductionmentioning
confidence: 99%